Zakat Collectible in OIC Countries for Poverty Alleviation: A Primer on Empirical Estimation - Salman Ahmed Shaikh (International Journal of Zakat, 2016)
This study estimates potential Zakat collectible in 17 member countries of the Organization of Islamic Cooperation (OIC). In our estimation, we found that the zakat to GDP ratio exceeds the poverty gap index to GDP (PGI-GDP) ratio in all but 3 countries, with poverty line defined at $1.25 a day. We also found that the zakat to GDP ratio exceeds the PGI-GDP ratio, except in 4 countries with poverty line defined at $2.00 a day. We also compared zakat to GDP ratio against poverty headcount ratio. According to our estimates, the Zakat to GDP ratio exceeds the poverty head count ratio to GDP (PHCR-GDP), except in 5 countries with poverty line defined at $1.25 a day. We also found that zakat to GDP ratio exceeds PHCR-GDP ratio except in 7 countries, with poverty line defined at $2.00 a day. Thus, the institution of Zakat has ample potential to contribute towards the alleviation of poverty. Lastly, we show that the aggregate resources pooled together from the potential Zakat collection in 17 OIC countries will be enough to fund resources for poverty alleviation in all 17 OIC countries combined. Keywords: Zakat, Fiscal Policy, Poverty, Redistribution